Mineralogical composition of three soil series from the Meghna floodplain of Bangladesh and the soil management implications (Bangladesh Journal of Scientific Research, 2011)
Key words: Floodplain soils; bulk mineral; clay minera; X-ray diffraction; management implicationBangladesh J. Sci. Res. 23(2): 115-128, 2010 (December)